Strengthening Moderate Islamic Religiousness in Habib Husein Ja'far's Digital Da'wah - Akhwanudin, Mohammad Khafid; Kholilurrohman, Muhammad; Fitriani, Tiara Bela; Afiantiy, Dwi Nur; Amelia, Shilfa; Purwanto, Genta Haru (International Tatho Academics, 2024)
This qualitative research aims to identify the value of strengthening moderate Islamic religiosity in digital da'wah delivered by Habib Ja'far. Indicators of religious moderation in Indonesia as an analysis theory. Habib Ja'far's da'wah content in the Jeda Nulis channel entitled